High-thermally conductive composite polyimide materials - Borshchov, V.M.; Listratenko, O.M.; Protsenko, M.A.; Tymchuk, I.T.; Kravchenko, O.V.; Syddia, O.V.; Slipchenko, M.I.; Chichkov, B.M. (Radiotekhnika, 2022)
This review is devoted to analysis of works in the field of creating electrically insulating heat-conducting polyimide composite films based on powders of micro-, submicro- or nano-sized fillers with high dielectric and heat-conducting properties for use as effective thermal interface materials in various electronic devices in instrument making. Particular attention is paid to studies on the influence of the size of nano- and microparticles of inorganic fillers on the heat-nducting, dielectric, and physical-mechanical properties of nanocomposite polyimide materials. The analysis of the results of work on the study of the dependence of thermal conductivity on the ratios of micron and nanosized particles in mixtures and their number in polyimides and on the conditions of their polymerization was carried out to confirm the possibility of increasing the thermal conductivity values of promising polyimide materials from 0.12 W/(m•K) up to 5¸10 W/ (m•K). It is noted that the highest thermal conductivity of industrially produced modern polyimide films on market does not exceed 0.75¸0.8 W/(m•K). The task of creating inexpensive, but high-quality heat-conductive polyimide composite materials with sufficiently high thermal conductivity without deteriorating their strength and ductility characteristics is currently relevant and technically in demand.